Adenosquamous Pancreatic Cancer: 10 Years of Experience in a Center - Milanetto, Anna Caterina; Sperti, Cosimo; Moletta, Lucia; Alaggio, Rita; Pedrazzoli, Sergio; Pasquali, Claudio (JOP. Journal of the Pancreas, 2012)
Context Pancreatic adenosquamous carcinoma (PASC) represents 0.4-4% of the exocrine pancreatic neoplasms and has a more aggressive behavior than ductal adenocarcinoma, but its natural history is unknown. Objective To evaluate clinical presentation, preoperative investigations, surgical approach, histological features and follow up in PASC. Methods We reviewed clinical data of patients who underwent pancreatic resection for PASC in the last decade in our Department. Results From January 2002 to December 2011 we performed 211 pancreatic resections for malignant cancer of the exocrine pancreas and 4 of them were PASC (1.8%). All patients (4 M, averaging 63.7 years; range 54-76 years) had a tumor located in the pancreatic head. Symptoms of presentation were upper abdominal pain (2/4), hyperglycemia (2/4) and jaundice (1/4). CA 19-9 was high in 2/4 patients without jaundice. All patients underwent pancreaticoduodenectomy (mean tumor size 3.4 cm) and in 3/4 cases a vascular resection was performed. In 2/4 cases a preoperative pancreatic biopsy was positive for pancreatic adenocarcinoma. Follow up to December 2011 (mean follow up 21.3 months). Two patients had an intra-abdominal bleeding in the perioperative period: one died after an early reoperation and the other died of tumor progression after 14 months. Another patient died with hepatic relapse (follow up 8 months) and the last one developed an urothelial cancer but is still alive (follow up 42 months). Conclusion Surgical treatment is the only reasonable therapeutic approach for PASC, but early relapse is frequent. The role of non-operative therapies for PASC is less clear. If preoperatively known, PASC could be candidate to neoadjuvant therapy.